2016
DOI: 10.1093/cercor/bhv321
|View full text |Cite
|
Sign up to set email alerts
|

Auditory to Visual Cross-Modal Adaptation for Emotion: Psychophysical and Neural Correlates

Abstract: Adaptation is fundamental in sensory processing and has been studied extensively within the same sensory modality. However, little is known about adaptation across sensory modalities, especially in the context of high-level processing, such as the perception of emotion. Previous studies have shown that prolonged exposure to a face exhibiting one emotion, such as happiness, leads to contrastive biases in the perception of subsequently presented faces toward the opposite emotion, such as sadness. Such work has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…We were curious as to whether the average listening or the average speaking proficiency measures were driving this association. As earlier mentioned, the FFA or the STS seems to be responsible for the perceptual narrowing observed during the ORE, and auditory signals seem capable of altering neural activity in both (Ethofer et al, 2006;Wang et al, 2016). We therefore hypothesised that listening proficiency might be better associated with the ORE than speaking proficiency.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…We were curious as to whether the average listening or the average speaking proficiency measures were driving this association. As earlier mentioned, the FFA or the STS seems to be responsible for the perceptual narrowing observed during the ORE, and auditory signals seem capable of altering neural activity in both (Ethofer et al, 2006;Wang et al, 2016). We therefore hypothesised that listening proficiency might be better associated with the ORE than speaking proficiency.…”
Section: Resultsmentioning
confidence: 76%
“…These tests have been widely used to test both neurotypical (Arnell & Dube, 2015;Palermo et al, 2016) and neuropsychological (Bate et al, 2014;Burns et al, in press;Burns, Martin, Chan, & Xu, submitted;Burns, Tree, & Weidemann, 2014;Kirchner, Hatri, Heekeren, & Dziobek, 2011;O'Hearn, Schroer, Minshew, & Luna, 2010) populations' face memory abilities, and are particularly useful as they can reveal subtle differences in performance that other tests fail to yield (Duchaine & Nakayama, 2006). We anticipate that increasing bilingual proficiency will lead to a diminishing ORE, with listening proficiency in particular being more strongly linked than speaking proficiency due to the fact that auditory signals modulate activity in the FFA (Ethofer et al, 2006;Wang et al, 2016) and STS (Deen, Koldewyn, Kanwisher, & Saxe, 2015;Démonet, Thierry, & Cardebat, 2005).…”
Section: Introduction 31mentioning
confidence: 96%
See 1 more Smart Citation
“…The prediction effect is important for crossmodal (Jessen and Kotz, 2013). Generally, emotional adaptation played a prediction role in crossmodal (Wang et al, 2017). We shall now investigate whether emotional adaptation can highly promote crossmodal integration and whether the difference between Vand A-leading cues can provide more helpful predictions of crossmodal integration for MADs.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, emotional recognition of crossmodal in MADs could be highly prompted by A-leading cues, especially the fearful sound, yet this dominance ceased to exist within HCs. It is suggested that the prediction of fearful sound played an important role in the crossmodal of MADs (Wang et al, 2017). This asymmetry between the visual-and auditory-leading cues suggested that there were separate, selectively recruited networks (Cecere et al, 2017).…”
Section: Discussionmentioning
confidence: 99%